Laboratory evaluation of some indigenous plant extracts as toxicants against red flour beetle, Tribolium castaneum Herbst - Mamun, MSA; Shahjahan, M; Ahmad, M (Journal of the Bangladesh Agricultural University, 2010)
Experiments were carried out to evaluate the toxicity of six botanicals, Bazna (Zanthoxylum rhetsa), Ghora-neem (Melia sempervirens), Hijal (Barringtonia acutangula), Karanja (Pongamia pinnata), Mahogoni (Swietenia mahagoni) and Neem (Azadirachta indica) against red flour beetle, Tribolium castaneum Herbst. Leaf and seed extracts were prepared by using acetone, methanol and water as solvents. The results showed that extracts of all the six plants had direct toxic effect on red flour beetle. Among them, Neem seed extract showed the highest toxic effect (mortality, 52.50%), whereas Hijal leaf extract possessed the lowest toxic effect (mortality, 22.24%). Among the solvents, acetone extract showed more toxic effect than other extracts. Seed extracts of respective plants were slightly more toxic than leaf extract. The effectiveness of most of the plant extracts increased proportionally with the increase of doses and decreased with time. Keywords: Plant extracts; Toxicity; Red flour beetle DOI: 10.3329/jbau.v7i1.4789 J. Bangladesh Agril. Univ. 7(1): 1-5, 2009